Parietal echinococcosis secondary to a previously operated lung cyst - Maissonave, Alberto (Cirugía del Uruguay, 2020)
The author presents the case of a patient who had six K. Hydraulics of the chest wall, conglomerates surrounding an old scar, which corresponded to the incision of an intervention done eight years ago to operate a K. H. of the lower left lobe of the lung. M. states the reasons that. They lead him to believe that this lung cyst is the primitive and that its approach and drainage (has been operated for a while) has been done. that the water fluid spread in the operative wound sow fertile scolices at who has followed his graft and hydatidation. He notes that if there is any doubt about the fertility of K. H. of the lung, this case would be an almost experimental proof of it. They are also evidence of this fertility, secondary bronchogenetic pulmonary hydatosis and secondary hydatosis of the pleura. Point out the extreme rarity of sowing the chest wall! consecutive to the operative interventions by K. H. of lung and the causes to which this fact is attributed. He points out that surely due to this rarity, there is a great lack of operational care for this fact. Indicates the prophylactic measures recommended in this regard.